Métodos analíticos associados ao controle de qualidade de suco de laranja natural - Avi, Dayane Cristina de Freitas (Universidade Federal de São Carlos, 2023)
Over the years, food agencies, governments and the population itself have sought to consume and guarantee increasingly safe and nutritious food, which is guaranteed by law and which meets the requirements of certifications. This is because having a better quality of life, well-being and vitality have become non-negotiable goals for end consumers. The citrus juice industries, especially those of orange juice, have used different approaches and analytical methods to ensure that: their production processes meet the requirements of Good Manufacturing Practices (GMP); its final product is free of contamination and for Brazilian juice to continue to be one of the key players in international trade. Therefore, the present work aimed to describe and evaluate, theoretically and experimentally, two of the main analysis methods, usually employed in the orange juice industry, to monitor chemical and microbiological contamination indicators in NFC-type products (Not- from-concentrate). Using iodometric titration, it was possible to monitor the concentrations of sanitizers used in the production process, ensuring that they worked with concentrations in the optimal range for a 95% confidence interval. With the colorimetric method, it was possible to determine the concentration of diacetyl present in the juice, noting a low microbiological contamination in the product (with experimental error also associated with a confidence interval of 95%). The methods used proved to be efficient for quality control and both meet the needs of the analysis industry with speed of execution and accuracy of results.
Analytical methods dedicated to the quality control of natural orange juice
Keywords: Indústria; Alimentos; Segurança; Contaminações; Titulação; Diacetil; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ANALITICA::TITIMETRIA